Patency of Aditus Ad Antrum in Chronic Otitis Media Mucosal Type Undergoing Tympanoplasty - Anuj Devkota,; Bishow Tulachan,; Anup Acharya,; Roshan Acharya, (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Chronic otitis media (COM) mucosal type is a prevalent condition characterized by chronic inﬂammation of the middle ear, often leading to persistent ear discharge and tympanic membrane perforation. This study aimed to evaluate the patency of the aditus ad antrum in patients undergoing tympanoplasty and assess various factors inﬂuencing its blockage. Understanding these factors will help optimize surgical outcomes and reduce the need for repeat procedures. MATERIAL AND METHODS A prospective observational study was conducted at the Universal College of Medical Sciences (UCMS), Bhairahawa, Nepal. Sixty patients with COM mucosal type undergoing tympanoplasty after optimal medical management were evaluated based on various factors. These factors included age, site and size of tympanic membrane perforation, duration of the disease, contralateral tympanic membrane status, middle ear mucosa status, and mastoid pneumatization. The patency of the aditus ad antrum was assessed intraoperatively, and data were collected using otoscopic examination and intraoperative ﬁndings. Statistical analysis was performed to identify associations between these variables and the blockage of the aditus ad antrum. RESULTS Sixty patients were enrolled in the study, comprising 44 males and 16 females, with a mean age of 43.82 years (range: 28-60 years). The average disease duration was 19.93 months (range: 8-60 months). Middle ear mucosa status showed 50% normal, 30.0% edematous, and 20.0% myringosclerosis. The patency status of the aditus ad antrum was not signiﬁcantly associated with gender, disease duration, contralateral TM status, or mastoid pneumatization, with p-values of 0.243, 0.424, 0.084, and 0.273, respectively. A signiﬁcant association was found with the middle ear mucosa status. These results indicate that middle ear mucosa status is a signiﬁcant factor inﬂuencing aditus ad antrum patency (p = 0.038). CONCLUSION The ﬁndings suggest that the necessity of mastoidectomy in tympanoplasty for COM mucosal type should be based on speciﬁc middle ear mucosa ﬁndings, rather than being a standard procedure for all patients.